Evaluation of the penetration of ciprofloxacin and amoxycillin into the bronchial mucosa. Issue 9 (September 1988) - Honeybourne, D; Andrews, J M; Ashby, J P; Lodwick, R; Wise, R
Abstract : The concentrations of two antibiotics, amoxycillin and ciprofloxacin, were measured by microbiological assay in serum and in bronchial mucosa obtained at fibreoptic bronchoscopy in 38 patients undergoing diagnostic bronchoscopy for a range of respiratory symptoms. Patients had taken one of the two drugs orally for four days before bronchoscopy. The percentage penetration of antibiotic from serum to bronchial mucosa was calculated as the ratio of drug concentration in bronchial tissue to that in serum x 100. Of the nine patients who took amoxycillin 500 mg thrice daily the mean (SD) percentage penetration was 75. This was significantly lower than the mean percentage penetration of 147 in 29 patients who took ciprofloxacin 500 mg twice daily. Ten patients were given a single intravenous dose of ciprofloxacin 200 mg one hour before bronchoscopy and the mean percentage penetration was 231. This study has shown that the quinolone antibiotic ciprofloxacin is concentrated in the bronchial mucosa.